Childbirth experience questionnaire 2: Validating its use in the United Kingdom. (January 2020) - Walker, Kate F.; Dencker, Anna; Thornton, Jim G.
Abstract: Objective: To validate the Childbirth Experience Questionnaire 2 (CEQ2) in the UK to see if it is an effective tool for evaluating labour experience. Study design: The CEQ2 and part of the Care Quality Commission Maternity Survey (2010) was sent to 475 women one month and six weeks after birth. It was tested for face validity among 25 postnatal mothers. Demographic data and delivery data was used to establish construct validity using the method of known-groups validation. The results of the scored CEQ2 sent out twice were used to measure test-retest reliability by calculating the quadratic weighted index of agreement between the two scores. Criterion validity was measured by calculating the Pearson correlation coefficient for the CEQ2 and Maternity Survey scores. Results: Face validity of the CEQ2 in a UK population was demonstrated with all respondents stating it was easy to understand and complete. A statistically significantly higher CEQ2 score for subgroups of women known to report a better birth outcome demonstrated construct validity. A weighted kappa of 0.55 demonstrated test-retest reliability. A Pearson correlation co-efficient of 0.56 demonstrated a moderate correlation between the results of the CEQ2 and the results of the 'gold standard' assessment of childbirth experience in the UK: the Maternity Survey and hence criterion validity. Conclusions: This study demonstrates that the Childbirth Experience Questionnaire version 2 (CEQ2) is a valid and reliable measure of childbirth experience in the UK population.